Clinical and pathological characteristics of Castleman disease: an observational study in a Spanish tertiary hospital. Issue 14 (6th December 2019) - González-García, Andrés; Patier de la Peña, José Luis; García-Cosio, Mónica; Sarhane, Yasmina; Sánchez Díaz, Cristina; Barbolla Díaz, Ignacio; López Rodríguez, Mónica; Moreno, María Ángeles; Villarubia, Jesús; Manzano, Luis
Abstract: Castleman disease (CD) represents a heterogeneous group of lymphoproliferative disorders that share well-defined histopathological features. An observational study of patients with CD was conducted. A total of 53 patients had CD: 20 had the unicentric form (UCD) and 33 the multicentric (MCD) variant; 10 of the latter cases were infected with human herpesvirus-8 (HHV-8) and 23 were idiopathic (iMCD). Median age differed between UCD and iMCD (30 vs. 49 years, p = .004). Males were completely predominant in HHV-8-associated MCD (100%), and females were more frequent in UCD (75 vs. 48%, p = .06). Relapses were more frequent in iMCD (57 vs. 10% UCD, p = .002), and mortality was significantly higher in iMCD and the HHV-8-associated form with respect to UCD. We conclude that UCD is a benign disorder of younger ages and female predominance, while iMCD represents a different entity with more disease relapses and higher mortality.